Kapasitas Memori Kerja dalam Pengambilan Keputusan - M. Dinah Charlota Lerik (Buletin Psikologi, 2016)
This paper will discussed the working memory model developed by Baddeley and Hitch. Baddeley’s claimed that working memory consists of three components: the central executive and the two slave systems, the phonological loop and visuospatial sketchpad. The other model is created by Cowan, which assumes that working memory includes a number of processes that can keep a limited amount of information accessible for a limited amount of time. To test a person’s working memory capacity, there have been many working memory span tasks. Few experiment will be discused about the amount of working memory load determines the heuris tic by a person who make decision, determine the conjuction fallacy and judgment.